A Prospective Study on Profile and Pattern of Electric Injuries Cases brought in RNT Medical College, Udaipur - Yogesh Sharma; Punit Jain (Indian Journal of Forensic Medicine & Toxicology, 2021)
It is well known fact that electricity is essential to everyday life, both home and on the job. Perhaps it hasbecome such a familiar part of daily life , most people don’t give much thought to it or how much our workdepends on a reliable source of electricity. More importantly , people tend to overlook the hazards thatelectricity poses and fail to treat it with the respect it deserves.A prospective study on profile of electric injuries cases was conducted at RNT Medical college Udaipur,Rajasthan from July 2019 to November 2020 to know about the incidence and pattern of electric injuriescases , also to study the manner of events, seasonal variation, population at high risk to be victims of electricinjury and to provide recommendation for developing useful safety programs to decrease the incidence. Outof the total 100 cases, 86 were male and 14 were female. 83 cases were of 11 year to 50 year age group. 68cases occurred at work place , out of which 62 were male and 6 were female and 32 cases occurred at home.40cases occurred in rainy season and 39 cases occurred in winter season and 21 cases occurred in summer.This study emphasizes on better implementation of electrical injuries control program in communities andincrease the awareness of people and also on use of safety equipments and protective measures. As our studysuggests that most of the electric injuries cases were preventable.